Criminal liability of collective entities – the Polish perspective - Baran-Wesolowska, Beata (European Integration Studies, 2023)
This paper aims to present the Polish perspective on the criminal liability of collective entities. The author refers to the legal nature of the criminal liability of collective entities. Also, the material prerequisites for the criminal liability of companies are scrutinized in this article. The legal status of companies’ internal investigation in the context of criminal liability of collective entities is also discussed.